2014
DOI: 10.1111/bre.12075
|View full text |Cite
|
Sign up to set email alerts
|

Deep vs. shallow controlling factors of the crustal thermal field – insights from 3D modelling of theBeaufort‐MackenzieBasin (ArcticCanada)

Abstract: Significant lateral variations in observed temperatures in the Beaufort-Mackenzie Basin raise the question on the temperature-controlling factors. Based on the structural configuration of the sediments and underlying crust in the area, we calculate the steady-state 3D conductive thermal field. Integrated data include the base of the relic permafrost layer representing the 0°C-isotherm, public-domain temperature data (from 227 wells) and thermal conductivity data. For >75% of the wells the predicted temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
(202 reference statements)
2
7
0
Order By: Relevance
“…The high heat flow at depths of 1,000–1,200 mbsl may therefore be the combined effect of higher radiogenic heat production and higher temperatures in the thick, lower conductivity sediment packages blanketing deeper crust at the continent‐ocean transition. This hypothesis is similar to what is suggested at the continent‐ocean transition to the west in the Beaufort‐Mackenzie Basin of Canada (e.g., Sippel et al, 2015), although the heat flow values observed on the Canada Margin are, on average, a factor of 1.5–3 lower. Sediment thickness is greatest at the U.S. Beaufort Margin ocean‐continent transition, where it likely exceeds 14 km (Mosher et al, 2012; Chian et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The high heat flow at depths of 1,000–1,200 mbsl may therefore be the combined effect of higher radiogenic heat production and higher temperatures in the thick, lower conductivity sediment packages blanketing deeper crust at the continent‐ocean transition. This hypothesis is similar to what is suggested at the continent‐ocean transition to the west in the Beaufort‐Mackenzie Basin of Canada (e.g., Sippel et al, 2015), although the heat flow values observed on the Canada Margin are, on average, a factor of 1.5–3 lower. Sediment thickness is greatest at the U.S. Beaufort Margin ocean‐continent transition, where it likely exceeds 14 km (Mosher et al, 2012; Chian et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, we cannot rule out other hypotheses. For example, the higher heat flow observed in water depths of 1,000–1,200 mbsf may be, in part, associated with deeper, tectonic phenomena, such as reactivation of the failed Dinkum Graben that helped establish the margin (Grantz & May, 1982), or thermal blanketing (e.g., Sippel et al, 2015). Geologic, seismic, and structural interpretations for the Beaufort Margin suggest large, potentially active growth faults exist along the shelf and upper margin with possible extension in the west and thrusting in the east (e.g., Grantz et al, 1979; Haimila et al, 1990; Hasegawa et al, 1979; Houseknecht & Bird, 2011; Houseknecht et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the Amerasian Basin, reduced surface heat flow toward the outer continental slope of the Beaufort Mackenzie Basin was reported by Jones et al [1990], and attributed to thinner crust and less radiogenic heat production. Recently, 3-D thermal modeling of the Beaufort Mackenzie Basin, constrained by temperature data from over 200 deep boreholes, also identified a decrease in thermal gradients as the crustal thickness decreases toward the ocean-continent transition [Sippel et al, 2015]. Regional and local variations in the heat flow data presented for the East Siberian continental slope are also likely driven by changes in crustal thickness and composition, as well as radiogenic inputs from the highly variable sedimentary cover (ranging from meters to kilometers thick).…”
Section: 1002/2016gc006284mentioning
confidence: 99%
“…This difficulty largely arises from the variability of the lithosphere in terms of structure and composition, parameters that are a product of the tectonic setting and evolution of the location of interest. One well-established strategy to investigate the present-day thermal field of a certain area is to integrate existing geophysical and geological data into 3-D structural models that provide the basis for numerical modeling, which simulates heat transport processes after setting boundary conditions and thermal properties according to the geological structure (e.g., Scheck-Wenderoth and Lamarche, 2005;Noack et al, 2013;Scheck-Wenderoth et al, 2014;Sippel et al, 2015;Balling et al, 2016).…”
mentioning
confidence: 99%